HUBUNGAN FUSSY EATING DAN EARLY CHILDHOOD CARIES - Praziandite, Muthiara (JURNAL MEDIA KESEHATAN, 2021)
Background: Fussy Eating is an usual problematic eating behavior among children, but it has negative impact to children’s health, including oral health. Early Childhood Caries (ECC) is the most common dental hard tissue disease. Prevalence of ECC in Indonesia is 90% (Riskesdas, 2018). Aim: the purpose of this study is to is to understand the association between Fussy Eating and ECC of children. Method: this study is observational with cross-sectional design. Sampling was conducted with purposive sampling and total sample is 165 children between 3-5 years old with their mother. Subscale Food Fussiness of Children Eating Behaviour Questionnaire (CEBQ) is used to measure Fussy Eating behaviour of children. ECC was measured by def-t index. Data analysis using chi-square test. Result: Prevalence of children with Fussy Eating is 50,9%. This study found that Fussy Eating was significantly associated with ECC(p-value 0,010; OR = 2,380; 95% CI 1,273-4,450). Conclusion: Fussy Eating contribute on development of ECC.